E-commerce application system at motorcycle showroom - Triraharjo B.; Nguyen P.T.; Perumal E.; Shankar K.; Abadi S.; Hashim W.; Maseleno A. (Blue Eyes Intelligence Engineering and Sciences Publication, 2023)
Bampringsewu Motor Showroom is a business engaged with sale of used motorcycles. The development of sale technology makes the company wants to expand its scope and provide convenience for its customers. Making a web-based application that can simplify and benefit businesses for their owner and customer. Business and sale can be done on a website to make it easier for company and customer, for example customer no longer need to come directly to the showroom to see the motorbikes in the showroom. The owner realizes that not all of customers can have a lot of time to be able to come directly to the showroom. Therefore, designing this website can be a media and convenience between owner and customer. BEIESP.